The quest for responsibility accountability and citizenship in complex organisations - Bovens, M. A. P. (Cambridge Cambridge University Press, 1998)
The modern world is dominated by complex organizations. In this book Mark Bovens analyzes the questions associated with the search for responsiblity within such organizations. In organizations with many people contributing in many different ways, how can we determine who is accountable for organizational behavior? How do we define responsible behavior within organizations? Can different notions of responsibility prevent abuses? His analysis is multidisciplinary, combining law, social science, ethics, and organizational design, and provides a number of suggestions for institutional reform.
Includes bibliographical references (p. 231-246) and indexes.
Keywords: Organizational sociology